When the rainy day is the worst hurricane ever: the effects of governmental policies on SMEs during COVID-19 - Belghitar, Yacine; Moro, Andrea; Radić, Nemanja (Springer, 2021)
We investigate the impact of COVID-19 on 42,401 UK SMEs and how government intervention affects their capability to survive the pandemic. The results show that, without governmental mitigation schemes, 59% of UK SMEs report negative earnings and that their residual life is reduced from 164 to 139 days. The analysis shows that government support scheme reduces the number of SMEs with negative earnings to 49% and allows extending the residual life for SMEs with negative earnings to 194 days. In addition, the support scheme reduces the number of jobs at risk in our sample by around 20%. However, our results suggest that weaker firms benefit more than strong ones. Besides, industries that are worst hit by COVID-19 are not those that benefit most from the government support scheme. We ascribe this result to the fact that the schemes do not discriminate between those firms that deserve support and those that do not deserve it.
Keywords: Government intervention; Economic crisis; Cash Small firms; COVID-19